Réponses

  • Omnes
  • Modérateur confirmé
2014-03-07T21:37:54+01:00
Salut,

6 ( x+1 )² - 3x - 9   =   ( 2x - 8 ) ( 3x - 5 )

6(x² + 2x +1) -3x - 9 = 6x² -10x - 24x + 40
6x² + 12x + 6 -3x - 9 = 6x² -34x + 40
6x² + 9x - 3 = 6x² - 34x + 40
6x² + 9x - 3 - 6x² + 34x - 40 = 0
43x - 43 = 0
43x = 43
x = 1

Bonne soirée !
2014-03-07T21:39:29+01:00
Salut :)

6 ( x+1 )² - 3x - 9   =   ( 2x - 8 ) ( 3x - 5 )

6 (x² + 2 x (x) x 1 + 1²) - 3x - 9 = 2x x 3x + 2x x (-5) - 8 x 3x - 8 x (-5)
6 (x² + 2x + 1) - 3x - 9 = 6x² - 10x - 24x + 40
6 x (x²) + 6 x 2x + 6 x 1 - 3x - 9 = 6x² - 34x + 40
6x² + 12x + 6 - 3x - 9 = 6x² - 34x + 40
6x² + 9x - 3 = 6x² - 34x + 40
6x² + 9x - 3 - 6x² = -34x + 40
9x - 3 + 34x = 40
43x - 3 = 40
43x = 40 + 3
43x = 43
x = 43/43
x = 1

J'espère t'avoir aidé(e)! :)